"Anak dara" : at the crossroads of gender and ethnic identity in Singapore. - Mohamed Latiff Mohamed Haikel Fansuri. (2012)
This study is focused on understanding the gendering practices that occur in Singapore Malay society through the exploration of the term “Anak Dara”, its implied meanings and its regulative framework. The exploration will be viewed through the experiences of individuals defined as “Anak Dara” with the intention of understanding this framework through the effects, implications and lived experiences of being defined as such. This study is focused on the Singaporean contemporary context from a gender and ethnicity perspective within a multicultural setting. It attempts to understand the concept of “Anak Dara” from the perspective of the insider as well as the outsider. Through interviews, this paper will show that the interpretation of “Anak Dara” differs across the respondents due to the fractured nature of Malay society and the negotiation of Malay identity in Singapore.